Reconstruction of Nature-Based Learning from the Perspective of Holistic Education in Elementary Schools - Retno Utari; Gading Suryadmaja (CV. Global Cendekia Inti, 2026)
The dominance of cognitively oriented instruction in elementary education has increasingly diminished students’ direct engagement with the natural environment. This condition contributes to the decline of ecological awareness, social sensitivity, experiential learning opportunities, and the holistic development of children. This study aimed to reconstruct nature-based learning within the framework of holistic education at the elementary school level. Employing a qualitative approach through library research, the study analyzed various scholarly sources related to holistic education, experiential learning, ecoliteracy, and nature-based pedagogy. The findings reveal that nature-based learning strongly aligns with the principles of holistic education because it simultaneously integrates cognitive, emotional, social, spiritual, and ecological dimensions. Nature functions not merely as a learning medium, but also as a living pedagogical space that facilitates contextual, reflective, collaborative, and meaningful learning experiences. Furthermore, the reconstruction of nature-based learning contributes to strengthening character education, ecological awareness, problem-solving skills, and the implementation of differentiated instruction within the Merdeka Curriculum framework. Therefore, nature-based learning can serve as an alternative pedagogical approach for developing holistic, contextual, and sustainable elementary education.